The Relationship Between Perceived Authoritarian Parenting Style And Obsessive-Compulsive Personality Disorder Symptoms Among University Students : The Mediating Effect Of Type-D Personality And Resilience - Kadhim, Ali Saad (2017)
This study aims to investigate the occurrence of mediating effect of Type-D personality (TDP) and resilience on the effect of perceived authoritarian parenting style (PAPS) on obsessive-compulsive personality disorders (OCPD) among undergraduate students in a university in Penang, Malaysia. A survey was conducted among 122 undergraduate students in academic year 2016, where participants were asked to complete a set of questionnaire that consisted of Parental Authority Questionnaire (PAQ), Type–D Personality scale (DS14), Five-Factor Obsessive Compulsive Inventory (FFOCI), and Connor–Davidson Resilience Scale (CD-RISC-25).